Biotransformation of phthalate plasticisers and bisphenol A by marine and freshwater fungi. Issue 5 (27th May 2022) - Cowan, Andrew; Carstens, Lena; Seiwert, Bettina; Schlosser, Dietmar
Abstract : Phthalate esters (PEs) are environmentally ubiquitous micropollutants that are used as plasticizers and additives in diverse consumer products. Considerable concern relates to their reported xenoestrogenicity and the microbial-based attenuation of environmental PE concentrations is of interest to combat harmful downstream effects. Fungal PE catabolism has received less attention than that by bacteria, and particularly marine fungal species remain largely overlooked in this respect. We have compared the biocatalytic and biosorptive removal rates of di-n-butyl phthalate (DBP) and diethyl phthalate (DEP), chosen as two environmentally prominent PE representatives (exhibiting differing structures and hydrophobicities), by marine- and freshwater fungal strains. Bisphenol A, both an extensively used plastic additive and prominent environmental xenoestrogen, was included as a reference compound due to its previously well-documented fungal degradation. Partial pathways for DBP metabolization by these ecophysiologically diverse ascomycetes were proposed with the help of UPLC-QTOF-MS analysis. Species-specific biochemical reaction steps contributing to DBP metabolism were also observed. The involved reactions include initial cytochrome P450-dependent monohydroxylations of DBP with subsequent further oxidation of related metabolites, de-esterification via either hydrolytic cleavage or cytochrome P450-dependent oxidative O-dealkylation, transesterification, and demethylation steps - finally yielding phthalic acid as a central intermediate in all pathways. Beyond previous research into fungal PE metabolism which emphasises hydrolytic de-esterification as the primary catabolic step, a prominent role of cytochrome P450 monooxygenase-catalysed reactions is established.